The Use of Natural Dyes from Beetroot Skin Extract (Beta Vulgaris) as Teaching Material on Cell Division for Senior High School Students - Adilla Nur Azizah; Putri Agustina; Suparti Suparti; Alanindra Saputra; Yasir Sidiq (Universitas Muhammadiyah Surakarta, 2020)
One of the Basic Competencies (KD) in Biology for Indonesian Senior High School is KD 4.12 which reads